2012
DOI: 10.2147/ijn.s34675
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembled supramolecular nano vesicles for safe and highly efficient gene delivery to solid tumors

Abstract: Abstract:The main obstacles for cationic polyplexes in gene delivery are in vivo instability and low solid-tumor accumulation. Safe vectors with high transfection efficiency and in vivo tumor accumulation are therefore highly desirable. In this study, the amphiphilic block copolymer poly(n-butyl methacrylate)-b-poly(N-acryloylmorpholine) was synthesized by reversible addition-fragmentation chain-transfer (RAFT) radical polymerization. The corresponding well-defined vesicles with narrow size distribution were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…In our work, we used lentiviral vectors encoding egFP as a dynamic fluorescent tracer but obtained a negative outcome, although we further opened skin-flap window and cut out the lungs for fluorescent imaging. one probable explanation was that the low aggregation of tumor nodules accounted for the negative results and the IVIS system was not fit for fluorescence imaging of tumors inside the mouse body (41,42), but rather the bioluminescent imaging (43). In the subcutaneous models, the reduction in tumor weight and tumor volume followed Livin gene silencing (9,21).…”
Section: Discussionmentioning
confidence: 99%
“…In our work, we used lentiviral vectors encoding egFP as a dynamic fluorescent tracer but obtained a negative outcome, although we further opened skin-flap window and cut out the lungs for fluorescent imaging. one probable explanation was that the low aggregation of tumor nodules accounted for the negative results and the IVIS system was not fit for fluorescence imaging of tumors inside the mouse body (41,42), but rather the bioluminescent imaging (43). In the subcutaneous models, the reduction in tumor weight and tumor volume followed Livin gene silencing (9,21).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the self-assembly mechanism, well-defined micelle and vesicle with surface targeting decorating were finely engineered. [98] We found that the temperature-regulated passive and mAb-tuned active dual targeting immunomicelles significantly enhanced intratumor accumulation and cellular uptake. The nanostructure and the dimension were also tailored to match the large endothelial cells gaps in tumors with enhanced permeability and retention (EPR).…”
Section: Well-defined Nanocarrier's Engineering For Immunotherapymentioning
confidence: 81%
“…Noted here, the mice with FITC administration at 0 hour were used as control. The in vivo images were observed with IVIS imaging system (excitation 500 nm) and recorded by a built-in CCD camera [ 31 ]. For further checking the tumor accumulation, the slides of the HSA/ADR and HSA-ADR NPS groups were anaesthetized by 1.5% isoflurane in 1 : 2 O 2 /N 2 .…”
Section: Methodsmentioning
confidence: 99%